Glass 2014
DOI: 10.1515/9783110298581.1
|View full text |Cite
|
Sign up to set email alerts
|

1. Influence of Thermal Prehistory on Crystal Nucleation and Growth in Polymers

Abstract: Observations regarding the effect of thermal history of crystallizing polymer melts onto the outcome of crystal nucleation and growth processes are investigated experimentally. Some results can be at least on a qualitative basis explained by classical nucleation theory (CNT) while others are not easy to understand in the framework of CNT. The origin of the respective problems and possible extensions of CNT to overcome them are briefly discussed. We chose polymers as model systems because they allow one a separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 149 publications
(323 reference statements)
3
26
0
Order By: Relevance
“…All higher cooling rates are supercritical and can be applied without introducing morphological changes on cooling. Nevertheless, also after supercritical cooling there may be different amounts of homogenously formed nuclei …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All higher cooling rates are supercritical and can be applied without introducing morphological changes on cooling. Nevertheless, also after supercritical cooling there may be different amounts of homogenously formed nuclei …”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, also after supercritical cooling there may be different amounts of homogenously formed nuclei. [9,32,34,61] In the second step, the crystallization behavior can be determined by cooling the sample from the melt to the temperature of interest and annealing it isothermally for a given time (see Figure 4). From the subsequent heating after annealing the enthalpy change during melting can be determined too; this reflects the enthalpy change during crystallization on annealing.…”
Section: Fast Scanning Chip Calorimetrymentioning
confidence: 99%
“…It was also found that occurrence of several other phenomenon is affected by local-region fluctuations. For example, Dzuba and Tsvetkov 10 reported the effects of these fluctuations on chemical reactions, and in a study of nucleation and crystallization by fast calorimetry (10 5 K/s), Schick and coworkers 20,21 found that nucleation and crystallization in the glassy state of some fast crystallizing polymers occur in the local-regions of molecular motions, i.e., in the regions where molecular motions are observed as the JG relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…When that occurs, its specific volume, entropy, enthalpy, and G decrease with time and the rate of decrease becomes slower as the amount of the crystalline phase formed increases. Nucleation occurs in randomly dispersed local regions in the bulk of an amorph [61][62][63][64][65][66], and the growth of the nuclei to crystals is slow and gradual. Crystal growth in a glass also causes local contraction, and the consequent internal (tensile) strains often cause the sample to develop micro-cracks or even fracture it.…”
Section: Effects Of Preparation Conditions and Structural Relaxationmentioning
confidence: 99%